Comparison of behavior, thermoregulation, and growth of pair-housed versus individually housed calves in outdoor hutches during continental wintertime - Kimberly J. Reuscher; Rekia S. Salter; Tadeu E. da Silva; Jennifer M.C. Van Os (Journal of Dairy Science, 2024)
ABSTRACT: Cold stress negatively affects the welfare of calves in outdoor hutches. No studies have examined the potential benefits of pair housing calves to buffer against cold stress. Our study evaluated the effects of pair versus individual housing on thermoregulatory, behavioral, and growth performance responses of calves in outdoor hutches during a Wisconsin continental winter. Forty-eight Holstein-Friesian heifer calves were enrolled into 1 of 2 housing treatments: individually (n = 16 calves) or pair housed (n = 16 pairs; 32 calves). Calves were fed milk twice daily, with ad libitum access to starter and water. Step-down weaning began on d 42 of life, and all milk was removed on d 54. Data collection continued through d 59. Calves were restricted inside a hutch (pair-housed calves in the same hutch) for 1 h during wk 4, 6, and 9 of life; internal hutch air temperature (T) was recorded with data loggers, and rectal temperature (RT) was recorded outside the hutch before and after restriction. On the subsequent 3 d in those weeks, calves' locations (outside or inside a hutch) were recorded at 15-min intervals using time-lapse cameras. Linear mixed models (change in T and RT after 1 h) and generalized linear mixed models with a β distribution (proportion of time spent inside hutches) were used to evaluate the fixed effects of housing treatment, week of life, and their interaction. For pair-housed calves, preference to be together was evaluated using one-sample t-tests comparing the proportion of time they were observed in the same location against 50% (chance, no preference), separately for each week of life. Predicted dry matter intake (DMI) of starter and body weight (BW) were standardized by day of life using regression models and used to calculate average daily gain (ADG) and feed conversion ratio (FCR; DMI of starter/ADG). Linear mixed models were constructed for each measure, separately for the preweaning, weaning, and postweaning periods, with a fixed effect of housing treatment; the models for BW included birth weight as a covariate. All mixed models included a random term for housing unit (individual or pair of calves) nested within treatment. Hutch T increased more after 1 h with pair-housed calves inside than with those housed individually (+2.3 vs. 1.4°C, respectively; standard error of the mean = 0.26°C). However, no treatment differences were detected in RT. Individually housed calves spent more time inside the hutches than pair-housed ones (93.9 vs. 90.7% of total time, respectively; standard error of the mean = 0.8%), and the latter chose to be together most of the time, regardless of location (90.0 ± 1.3%, 88.6 ± 1.2%, and 79.4 ± 4.2% in wk 4, 6, and 9 of life, respectively). After weaning, there was some evidence suggesting that pair-housed calves had greater starter DMI than those housed individually. No effects of housing type were found on FCR, BW, or ADG. Our study is the first to explicitly examine the potential benefits of pair housing for alleviating cold stress in outdoor-housed dairy calves, and we found limited evidence in support of our hypotheses.